Molecular screening of Bangladeshi rice (oryza sativa l.) genotypes for bacterial leaf blight - Jannat, Kazi Meftahul; Khatun, Khadiza; Islam, Md. Rafiqul; Koly, Mokaram Hanifa; Naher, Nazmun (The International Journal of Biotechnology, 2025)
Bacterial leaf blight is a major threat to rice production worldwide, especially in Bangladesh. The best approach for plant breeders to address this issue is to develop resistant varieties using the available resistant gene pool. The current study used DNA marker technology to identify major BLB resistance genes in Bangladesh’s landraces and local rice cultivars. We used reported molecular markers to assess the presence of BLB resistance genes (Xa4, Xa5, Xa7, Xa13, and Xa21) in genotypes. The results showed that the Xa4 gene was present in 10 genotypes. Two of these genotypes also gave positive bands for the Xa5 gene, while three showed positive results for the Xa13 gene. Among these, one genotype contained Xa13 and Xa5 genes, and another had Xa7 and Xa21 genes. Additionally, two genotypes were found to carry both the Xa7 and Xa13 genes. The phylogenetic tree illustrates the genetic relationships among 41 rice genotypes, grouping them into four main clusters. Within these clusters, genetically similar genotypes tend to be grouped. This study offers valuable insights for identifying genotypes that carry multiple resistance genes, which could serve as a potential resource for breeding programs to develop rice genotypes resistant to bacterial leaf blight.